Advances in biomembranes and lipid self-assembly. - Iglic, Ales; Rappolt, Michael; Garcia-Saez, Ana (Academic Press, 2021)
Advances in Biomembranes and Lipid Self-Assembly, Volume 34, formerly titled Advances in Planar Lipid Bilayers and Liposomes, provides a global platform for the study of cell membranes, lipid model membranes and lipid self-assemblies, from the micro- to the nanoscale. As planar lipid bilayers are widely studied due to their ubiquity in nature, this book presents research on their application in the formulation of biomimetic model membranes, and in the design of artificial dispersion of liposomes. Chapters cover Physical properties of SOPC lipid membranes containing cholesterol by molecular dynamics simulation, Exciting membrane fluctuations - more than thermal stimulation, Fluctuations shaping bio-membrane adhesion, and more.